2016
DOI: 10.1515/secm-2013-0291
|View full text |Cite
|
Sign up to set email alerts
|

Influence of injection molding parameters on electrical resistivity of carbon nanotube reinforced polycarbonate

Abstract: Electrical properties of plastic products can be adjusted by adding a certain amount of carbon nanotubes (CNT) in the injection molding process. However, injection molding parameters should be arranged carefully due to their influence on electrical properties of CNT-reinforced plastic composites. In this study, polycarbonate/CNT nanocomposites, having three different CNT concentrations (1, 3 and 5 wt%), were produced and injection molded by using three different injection temperatures and speeds to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This was also demonstrated for CNT-based nanocomposites [ 12 ]. Several studies have shown that the variation of the processing condition of injection-molded components, manufactured with CNT-based nanocomposites, can lead to drastic modification of the electrical conductivity, especially when the CNT content is in the range of the electrical percolation [ 13 , 14 , 15 , 16 , 17 , 18 ]. Villmow et al [ 16 ] studied injection-molded polycarbonate-based CNT nanocomposites, demonstrating that lowering the cooling rate and residence time seems to favor the attainment of higher electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…This was also demonstrated for CNT-based nanocomposites [ 12 ]. Several studies have shown that the variation of the processing condition of injection-molded components, manufactured with CNT-based nanocomposites, can lead to drastic modification of the electrical conductivity, especially when the CNT content is in the range of the electrical percolation [ 13 , 14 , 15 , 16 , 17 , 18 ]. Villmow et al [ 16 ] studied injection-molded polycarbonate-based CNT nanocomposites, demonstrating that lowering the cooling rate and residence time seems to favor the attainment of higher electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] Many methods to produce such nanocomposite materials can be listed. Among them, melt blending [23][24] offers a simple way of dispersing nanoparticles in a polymer matrix and it is now widely used in industries to manufacture polymer parts [25][26][27][28] . A weight percentage higher than the percolation threshold can be used to obtain electrically conductive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods to produce such nanocomposite materials can be listed. Among them, melt blending , offers a simple way of dispersing nanoparticles in a polymer matrix and it is now widely used in industries to manufacture polymer parts. A weight percentage higher than the percolation threshold can be used to obtain electrically conductive materials. For example, Seo et al , stated that once the percolation threshold is exceeded (between 1 and 2 wt %), the volume resistivity drops from 10 9 Ω cm to reach a value of 10 3 Ω cm.…”
Section: Introductionmentioning
confidence: 99%